A Study of Frictional Forces between Orthodontic Brackets and Archwires - Alison Downing; J.F. McCabe; Peter H. Gordon (1994)
The differences in magnitude of static and kinetic frictional forces generated by 0·022 × 0·030-inch stainless steel (Dentaurum ® ) and polycrystalline ceramic (Transcend ® ) brackets in combinntion with archwires of different sizes (0·018 inch and 0·019 × 0·025 inch) and materials (stainless steel, nickel-titanium, and beta-titanium) at a constant ligature force were investigated. A friction-testing assembly using the Instron machine was used. In all cases, the static frictional force was greater than the kinetic frictional force. There were no significant differences in the frictional forces generated by stainless steel and polycrystalline ceramic brackets. Beta-titanium archwires produced greater frictinal forces than the other two materials. Increasing the archwire diameter increased the frictional force.